Effect Of Epigallocatechin-3-Gallate (EGCG) On The Number Of Macrophage Cells In Inflammation Of Pulp With Mechanical Injury - Kun Ismiyatin; Devi Eka Juniarti; Djoko Agus Purwanto; Adecha Ekalipta Primazafira (Universitas Airlangga, 2020)
Background: Pulpitis is an inflammatory pulp that can occur due to mechanical trauma that causes perforation of the pulp. Treatment of pulpitis Emergency frequently using Eugenol. High concentrations of Eugenol have a cytotoxic effect that causes local necrosis and inhibits the recovery process. An alternative consideration with Epigallocatechin 3-gallate (EGCG) which has good antioxidant properties and increases the complexity of inflammation by inhibiting the production of inducible nitric oxide synthase (iNOS) and nitric oxide so that levels migration of inflammatory cells to the area of injury will decrease and inflammation will occur shorter then initiates the proliferation so the recovery process and tissue repair will be more rapidly occurring. One of the cells that support tissue repair is macrophages. Purpose: this study aims to explain the effect of EGCG on the number of macrophage cells in pulp inflammation with mechanical injury. Methods: The study used 24 Wistar rats teeth divided into four groups, namely control (C), and 3 treatment groups T1, T2, and T3. Each group consisted of 6 rats prepared, then T1 was named EGCG hydrogel 60 ppm, T2 was given EGCG hydrogel 90 ppm, while T3 was given EGCG hydrogel 120 ppm. On the 3rd day, Wistar rats were decapitated to continue making HPA preparations. Results:This study showed a significant difference in each group (p< 0.05) using One-Way Anova analysis. Conclusion: EGCG hydrogel 90 ppm is effectivein increasing the number of macrophage cells.